6a+7=2a-1

Simple and best practice solution for 6a+7=2a-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6a+7=2a-1 equation:



6a+7=2a-1
We move all terms to the left:
6a+7-(2a-1)=0
We get rid of parentheses
6a-2a+1+7=0
We add all the numbers together, and all the variables
4a+8=0
We move all terms containing a to the left, all other terms to the right
4a=-8
a=-8/4
a=-2

See similar equations:

| 12x+13=-9x+20 | | 5(2x−3)=15 | | 12x+13=-9+20 | | 7r−5r=6 | | -51=7(x-3) | | 75x=450+25x | | x+30+2x+10+2x-30=360 | | -2(x-1)+2x=3-(x-1) | | 4x-5=3(2+x)-4x | | 6+(3x+7)=4(-2x+1) | | -t+6=5t-12 | | 7/(x+3)=-21/(x+7) | | x+3x=94 | | (x+3)/(3x-1)=1 | | (x+3)/3x-1=1 | | 5(2x-1)=4x+2(x+5)-3 | | 20-3s=-10-6s | | 7x2-90x-112=0 | | 20-3=-10-6s | | (x+8)/5=x-8 | | -2(50-6x)=4(2x+12) | | -2(50-6x)=4(2x+12 | | 5x-2(5x-2)=4x+5 | | 3d=-18=d | | 2x+(x-4)=0 | | 0r-7=r+5 | | 8(x-4)-6(x+9)=9(x+11)-8(x-5) | | 2(2+x)+(4x-1)×3=10x-7 | | -5y+8=2 | | 4(t+4=116t-72-68t | | (2x-1)(3x-6)=0 | | 15q=24-9q |

Equations solver categories